2019
DOI: 10.4149/gpb_2019041
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of microRNA-10a mediates the anti-tumor effect of icaritin in A549 cells via the PTEN/AKT and ERK pathway

Abstract: Icaritin, a prenylflavonoid derivative from Epimedium Genus, has been reported to exhibit tumor inhibitory effects on many types of tumor cells. Numerous studies have demonstrated that microRNAs (miRs) involve in the biological process of carcinogenesis by controlling expression of their target mRNAs to facilitate tumor growth, invasion, angiogenesis, and immune evasion. miR-124 was reported to involve in the icaritin-induced mitochondrial apoptosis in human carcinoma cells. However, the roles of other miRs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…The AKT/ERK pathway was highly expressed in PC and associated with an unfavorable prognosis (41,42). Additionally, previous studies confirmed that the AKT/ERK pathway was suppressed by PTEN (43)(44)(45). In the present study, the phosphorylation level of AKT and ERK were inhibited following silencing of miRNA-1297.…”
Section: Discussionsupporting
confidence: 79%
“…The AKT/ERK pathway was highly expressed in PC and associated with an unfavorable prognosis (41,42). Additionally, previous studies confirmed that the AKT/ERK pathway was suppressed by PTEN (43)(44)(45). In the present study, the phosphorylation level of AKT and ERK were inhibited following silencing of miRNA-1297.…”
Section: Discussionsupporting
confidence: 79%
“…Kaempferol can inhibit Matrix metalloproteinase (MMP)-2 activity of human A549 lung cancer cells [23]. Icaritin can be regulated by microRNA-10a the phosphatase and tensin homolog deleted on chromosome ten (PTEN/Akt) and extracellular signal-regulated kinase (ERK) pathway to inhibit human A549 lung cancer cells [24]. Quercetin can play an anti-cancer role in a variety of ways.…”
Section: Lung Cancermentioning
confidence: 99%
“…MiRNAs have been considered to play important roles in the progression of multiple diseases, including NSCLC [28,29]. In this study, we found that downregulation of miR-188-3p could partially reversed the antitumor effect of FGF12-AS2 knockdown.…”
Section: Discussionmentioning
confidence: 60%